Literature Review: Analysis of The Jigsaw Model in Improving Elementary School Students' Reading Skills in Indonesian Language Subject - Syafputri, Syafputri; Oktafiyanti , Trisna Indah; Rahma , Izra Aulia; Rahmadhansyah , Adrian; Qodri, Rijalul; Nurrahman, Habib; Rifaldi, Ahmad; Bramantio, Dimas; Pebriana, Putri Hana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This article examines the effectiveness of the Jigsaw learning model in improving the reading skills of elementary school students in the Indonesian language subject, based on a review of 20 related research journals. It was found that the Jigsaw method can enhance students' ability to comprehend texts, expand their vocabulary, and encourage active participation and collaboration in the classroom. However, its implementation faces challenges, such as the heterogeneity of students' abilities, which requires good classroom management to ensure that every student is engaged and benefits maximally. Another challenge is the need for thorough preparation by teachers in task distribution, group organization, and strategies to facilitate discussions. Supporting studies indicate that Jigsaw can improve students' overall academic skills, including their social and emotional aspects. This article suggests that teachers should be more flexible in designing learning groups that suit students' characteristics and create an inclusive and collaborative classroom atmosphere. Overall, despite the challenges, the Jigsaw method proves effective in developing students' reading skills, as long as it is implemented with proper management and attention to students' diverse abilities.